Pathogenesis and management of gastrointestinal inflammation and fibrosis: from inflammatory bowel diseases to endoscopic surgery - Kentaro Iwata; Yohei Mikami; Motohiko Kato; Naohisa Yahagi; Takanori Kanai (BMC, 2021)
Abstract Gastrointestinal fibrosis is a state of accumulated biological entropy caused by a dysregulated tissue repair response. Acute or chronic inflammation in the gastrointestinal tract, including inflammatory bowel disease, particularly Crohn's disease, induces fibrosis and strictures, which often require surgical or endoscopic intervention. Recent technical advances in endoscopic surgical techniques raise the possibility of gastrointestinal stricture after an extended resection. Compared to recent progress in controlling inflammation, our understanding of the pathogenesis of gastrointestinal fibrosis is limited, which requires the development of prevention and treatment strategies. Here, we focus on gastrointestinal fibrosis in Crohn's disease and post-endoscopic submucosal dissection (ESD) stricture, and we review the relevant literature.